Empirical Study for Capturing and Allocating Significant Risk Factors in School Construction Projects in Iraq (Journal of Engineering, 2023)
In Iraq, more than 1031 school projects have been halted due to disputes and claims resulting from financial, contractual, or other issues. This research aims to identify, prioritize, and allocate the most critical risk factors that threaten these projects’ success for the duration (2017-2022). Based on a multi-step methodology developed through systematic literature reviews, realistic case studies, and semi-structured interviews, 47 risk factors were identified. Based on 153 verified responses, the survey reveals that the top-ranked risk factors are corruption and bribery, delaying the payments of the financial dues to the contractors or sub-contractors, absence of risk management strategy, multiple change orders due to changing designs and specifications during construction; inaccuracy in time and budget estimation; construction material price; financial and economic crisis/financial instability; selecting the contractor only based on the lowest bid, regardless of technical competence; instability within the political system of the government/instability of the government as a client; foreign exchange rates fluctuate against the Iraqi dinar. The study also showed that the respondents recommended allocating four risks to the owner, eight risk factors to the contractor, one risk to the consultant, and 32 factors allocated as shared. The study concluded that the results could help identify the most critical risks facing this type of project and the contracting party that can bear the risks and manage them efficiently.